Skin resistance to water gain and loss has changed in cane toads (Rhinella marina) during their Australian invasion. Issue 23 (11th October 2020) - Kosmala, Georgia K.; Brown, Gregory P.; Shine, Richard; Christian, Keith
Abstract: The water‐permeable skin of amphibians renders them highly sensitive to climatic conditions, and interspecific correlations between environmental moisture levels and rates of water exchange across the skin suggest that natural selection adapts hydroregulatory mechanisms to local challenges. How quickly can such mechanisms shift when a species encounters novel moisture regimes? Cutaneous resistance to water loss and gain in wild‐caught cane toads ( Rhinella marina ) from Brazil, USA (Hawai'i) and Australia exhibited strong geographic variation. Cutaneous resistance was low in native‐range (Brazilian) toads and in Hawai'ian populations (where toads were introduced in 1932) but significantly higher in toads from eastern Australia (where toads were introduced in 1935). Toads from recently invaded areas in western Australia exhibited cutaneous resistance to water loss similar to the native‐range populations, possibly because toads are restricted to moist sites within this highly arid landscape. Rates of rehydration exhibited significant but less extreme geographic variation, being higher in the native range than in invaded regions. Thus, in less than a century, cane toads invading areas that impose different climatic challenges have diverged in the capacity for hydroregulation. Abstract : The invasion of cane toads from South America to Hawai'i and Australia has been accompanied by substantial shifts in the ability of the skin to restrict rates of water flow. Over a timeframe of less than a century, the toad invasion has generated major changes in a fundamental aspect of rates of abiotic exchange between the organism and its environment.